An integrated food and land-use system approach to meet Ethiopia’s long-term climate mitigation and development goals - Mulatu, Kalkidan Ayele; Getaneh, Yonas; Abera, Wuletawu; Chemarin, Charlotte; Diaz, Maria; Cozza, Davide (2025)
Ethiopia’s food security and climate change mitigation objectives are central to its national development strategies and global commitments, particularly within the Agriculture, Forestry, and Other Land Uses (AFOLU) sector. Yet, without coherent implementation, these goals risk producing conflicting outcomes. Identifying pathways that allow Ethiopia to meet both food security and climate change mitigation objectives—while effectively managing trade-offs and leveraging synergies—is therefore essential. This requires alignment with the net-zero 2050 vision under the Long-Term Low Emissions Development Strategy (LT-LEDS), Ethiopia’s 10-year development plan, as well as the country’s Food System Transformation and Nutrition goals (EFSTN), policies that converge around climate change. Using the Food, Agriculture, Biodiversity, Land, and Energy (FABLE) framework, the Alliance Bioversity International – CIAT, with the support of the Sustainable Development Solutions Network (SDSN), developed two integrated pathways to project food production for milestone years (2030 and 2050): Business-as-Usual (BAU) and LTLEDS-EFSTN pathway. These pathways were assessed against key agri-food system indicators, including food security and healthy diets, land-use dynamics, and greenhouse gas (GHG) emissions. The scenarios incorporate multiple drivers such as population growth, calorie demand, crop and livestock productivity, production systems, irrigation, afforestation, and deforestation trends. Findings indicate that while both BAU and LTLEDS-EFSTN pathways can meet Ethiopia’s food security needs, only the LTLEDS-EFSTN pathway enables the achievement of a net carbon sink from the AFOLU sector due to the expansion of forest cover and moderated cropland growth. Realizing these outcomes will depend on unlocking critical enablers within the AFOLU sector, including improved crop productivity, adoption of climate-smart agricultural practices, accelerated afforestation and land restoration, and more efficient livestock management. Aligning food security and climate objectives will further enable the design of Nationally Determined Contributions (NDCs) and Long-Term Low Emission Development Strategies (LT-LEDS) that are both climate-resilient and responsive to Ethiopia’s food and nutrition needs.